Investigation of eight cellulose nanomaterials' impact on Differentiated Caco-2 monolayer integrity and cytotoxicity. (August 2022) - Mortensen, Ninell P.; Moreno Caffaro, Maria; Davis, Klinton; Aravamudhan, Shyam; Sumner, Susan J.; Fennell, Timothy R.
Abstract: The potential applications of cellulose nanomaterials (CNMs) as food additives or in food packaging, present a possible source of human ingestion. While micron- and macro-scale cellulose products are classified as Generally Regarded As Safe, the safety of ingested nano-scale cellulose is largely unknown. Using fully differentiated Caco-2 cells, the perturbation of intestinal barrier function and cytotoxicity was investigated for four nanocellulose crystals (CNCs) and four nanocellulose fibrils (CNFs) following 24 h of exposure at 50 μg/mL. Scanning electron microscope showed some aggregation of both CNCs and CNFs. X-ray photoelectron spectroscopy analyses showed that carbon and oxygen were the main elements. The zeta-potential for CNMs formulated in cell culture medium showed a negative surface charge. Two CNMs increased cell membrane permeability and three CNMs decreased the cell metabolic activity. While three CNMs lead to cytotoxic responses, no changes in apparent permeability coefficient (Papp ) for dextran or tight junction integrity were found. Our results show that three CNMs induce cytotoxicity in differentiated Caco-2 cells, demonstrating the need to understand the role of size and shape. The interaction between CNMs and the intestinal epithelium needs to be evaluated to understand potential intestinal barrier dysfunction and resulting health implications following CNM ingestion.